Tectonic Deep Anterior Lamellar Keratoplasty to Treat Corneal Perforation and Descemetocele from Microbial Keratitis - Nguyen HT (Dove Medical Press, 2021)
Hong The Nguyen,1,2 Ngoc Dong Pham,3 Tung Quoc Mai,2 Hang Thi Thuy Do,3 Duong Thi Nga Nguyen,3 Peter McCluskey,4 Trong Van Pham2 1Department of Ophthalmology, 108 Military Central Hospital, Hanoi, Vietnam; 2Department of Ophthalmology, Hanoi Medical University, Hanoi, Vietnam; 3Department of Cornea, Vietnam National Eye Hospital, Hanoi, Vietnam; 4Department of Ophthalmology, University of Sydney, Sydney, NSW, AustraliaCorrespondence: Tung Quoc MaiDepartment of Ophthalmology, Hanoi Medical University, 1 Ton That Tung Street, Hanoi, 100000, VietnamTel +84 915644181Email maiquoctung@hmu.edu.vnPurpose: To evaluate the result of tectonic deep anterior lamellar keratoplasty (DALK) for keratitis with perforation and descemetocele.Patients and Methods: A prospective clinical study of 36 patients (36 eyes) treated with tectonic DALK for corneal perforation or descemetocele from microbial keratitis managed at the Vietnam National Eye Hospital over a two-year period. The surgical technique was manual lamellar dissection. The grafts were harvested from the anterior corneal cap of pre-cut donor tissues used for DSAEK or donor corneas with a low endothelial cell count.Results: A mean age was 55.36 ± 13.98 years (ranged from 25 to 75 years). Female gender represented 52%. causative agents were herpes simplex virus (58.3%), bacteria (22.2%), fungi (13.9%) and microsporidia (5.6%). There were 24 eyes with descemetocele (66.7%) and 12 with perforation (33.3%). There were 33 successful cases (91.7%) and 3 failed cases (8.3%). Best corrected visual acuity (BCVA) improved in 28 eyes (84.8%). The range of post-operative BCVA was from hand motions to 20/70. Eleven eyes (33.3%) attained vision 20/200 and higher. Clear graft was obtained in 15 eyes (45.5%), while mild or severe graft opacity was observed in 14 eyes (42.4%), and 4 eyes (12.1%), respectively. Surgical complications included descemet rupture (20.8%), pseudo anterior chamber (41.6%), persistent corneal epithelial defects (8.3%), reinfection (11.1%), glaucoma or ocular hypertension (5.6%) and cataract (8.3%).Conclusion: The study demonstrates that DALK is an effective procedure to treat corneal descemetocele, especially when an urgent penetrating keratoplasty (PKP) cannot be performed.Keywords: deep anterior lamellar keratoplasty, DALK, descemetocele, corneal perforation, corneal transplantation